The Influence Of Cash Turnover, Receivables Turnover, And Inventory Turnover On Profitability In Food And Beverage Sub-Sector Manufacturing Companies Listed On The Indonesia Stock Exchange (IDX) - Hasanah, Nurfitratun; Rimawan, M; Muniarty, Puji (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
This study examines the impact of cash turnover, receivables turnover, and inventory turnover on profitability in manufacturing companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Facing increasingly intense competition, companies in this sector need to demonstrate high management effectiveness, measured through profitability ratios such as Return On Assets (ROA). ROA assesses how efficiently a company utilizes its assets to generate profits. Additionally, activity ratios such as cash turnover, receivables turnover, and inventory turnover provide insights into the efficiency of asset utilization in generating revenue. This study uses data from ten manufacturing companies in the food and beverage sub-sector over the period 2020-2022. The results show that, partially, cash turnover and receivables turnover have a significant impact on profitability, whereas inventory turnover does not have a significant impact. Simultaneously, cash turnover, receivables turnover, and inventory turnover collectively have a significant impact on profitability. These findings underscore the importance of efficient management of cash and receivables to enhance profitability in Indonesia's food and beverage industry. The abstract clearly and concisely conveys the essence of the study, providing essential insights for readers to determine its relevance to their needs.